The tale on the tongue of animals in the poetry of Mohammad Osman Jalal (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The book " Awakening eyes in Proverbs and Preaching" by Mohamad Osman Jalal is one of the literary works of the nineteenth century which is a linguistic content for various cultural currents and tributaries that influenced the Egyptian environment. The causes of the modern literary renaissance, from education, research, translation, journalism and others to face the remnants of the intellectual and linguistic legacy of the ages of foreign sovereignty.It can be said that this book is one of the first translated contributions that paved the way for the creation of children's literature in the modern Arabic literature in Egypt through the arabization of some animal tales from the tales of the French poet Lafontaine.                                     The poet Mohammad Othman Jalal  did not stop at the limits of literal translation, and did not commit to the transfer of the stories as they are in their foreign origins. He even deleted them and amended them. He also came close to the Egyptian soul. He expressed this through systems and pieces of his writings, .